Thermodynamics Analysis of Unsteady MHD Mixed Convection with Slip and Thermal Radiation over a Permeable Surface - Muhammad, Ahmad; Makinde, Oluwole Daniel (Diffusion and defect data. Solid state data. Pt. A, Defect and diffusion forum, 2017)
This paper discusses the thermodynamics irreversibility in an unsteady hydromagnetic mixed convective flow of an electrically conducting optically dense fluid over a permeable vertical surface under the combined influence of thermal radiation, velocity slip, temperature jump, buoyancy force, viscous dissipation, Joule heating and magnetic field. The governing partial differential equations are reduced to ordinary differential equations by using similarity variable. A local similarity solution is obtained numerically using shooting technique coupled with Runge-Kutta Fehlberg integration method. The influence of various thermophysical parameters on velocity and temperature profiles, skin friction, Nusselt number, entropy generation rate and Bejan number are presented graphically and discussed quantitatively. It is found that velocity slip, surface injection and temperature jump can successfully reduce entropy generation rate in the presence of an applied magnetic field. A comparison of numerical solution is made with the exact solution under a special case scenario and excellent agreement is found.